Genome‐wide DNA methylation analysis using MethylCap‐seq in canine high‐grade B‐cell lymphoma. Issue 6 (8th October 2020) - Hsu, Chia‐Hsin; Tomiyasu, Hirotaka; Lee, Jih‐Jong; Tung, Chun‐Wei; Liao, Chi‐Hsun; Chuang, Cheng‐Hsun; Huang, Ling‐Ya; Liao, Kuang‐Wen; Chou, Chung‐Hsi; Liao, Albert T. C.; Lin, Chen‐Si
Abstract: DNA methylation is a comprehensively studied epigenetic modification and plays crucial roles in cancer development. In the present study, MethylCap‐seq was used to characterize the genome‐wide DNA methylation patterns in canine high‐grade B‐cell lymphoma (cHGBL). Canine methylated DNA fragments were captured and the MEDIUM‐HIGH and LOW fraction of methylated DNA was obtained based on variation in CpG methylation density. In the MEDIUM‐HIGH and LOW fraction, 2144 and 1987 cHGBL‐specific hypermethylated genes, respectively, were identified. Functional analysis highlighted pathways strongly related to oncogenesis. The relevant signaling pathways associated with neuronal system were also revealed, echoing recent novel findings that neurogenesis plays key roles in tumor establishment. In addition, 14 genes were hypermethylated in all the cHGBL cases but not in the healthy dogs. These genes might be potential signatures for tracing cHGBL, and some of them have been reported to play roles in various types of cancers. Further, the distinct methylation pattern of cHGBL showed a concordance with the clinical outcome, suggesting that aberrant epigenetic changes may influence tumor behavior. In summary, our study characterized genome‐wide DNA methylation patterns using MethylCap‐seq in cHGBL; the findings suggest that specific DNA hypermethylation holds promise for dissecting tumorigenesis and uncovering biomarkers for monitoring the progression of cHGBL. Graphical Abstract: Using Methyl‐cap next‐generation sequencing revealed the pathogenesis and potential monitoring methylated DNA markers for canine B cell lymphoma.